Functional microbial agents enhance ethanol contents and regulate the volatile compounds in Chinese Baijiu. (December 2021) - Hong, Lixia; Fu, Guiming; Liu, Ting; Chen, Yanru; Wu, Shengwen; Cai, Wenqin; Xie, Zijun; Wan, Yin
Abstract: In this study, functional microbial agents (FMA) with different ester-producing yeasts as variables were used instead of traditional Daqu to simulate the solid-state fermentation (SSF) of special-flavor Baijiu . The effects of FMA on the ethanol contents, volatile compounds and microbial community of Jiupei after 30 days of brewing were studied. Results showed that the ethanol contents in Jiupei with functional microbial agent groups (FMG) were higher than that of the control group with traditional Daqu (G5), and the ethanol content in Jiupei using the agents fortified with Wickerhamomyces anomalus (G3) was the highest (3.67% v/v). Results of high-throughput sequencing technology showed that Lactobacillus genus was dominant bacterial genus in the bacterial community, and the relative abundance of Lactobacillus genus in Jiupei with G3 was 87.0%, which was similar to that in Jiupei with G5 (87.6%). The content of volatile compounds in Jiupei with G3 was 136.02 mg/kg, which was the highest in Jiupei with FMG and the closest to the Jiupei with G5. These results showed that the use of FMA to replace traditional Daqu could increase the yield of ethanol in Chinese Baijiu brewing, and the volatile compounds in Jiupei with G3 were close to that of the G5. Highlights: Compared to the traditional Daqu, the ethanol content of FMG was the highest. Compared to the traditional Daqu, the volatile compounds of FMG changed. Compared to the traditional Daqu, the microbial structure of FMG remained steady.